Radiosynthesis of the anticancer nucleoside analogue Trifluridine using an automated 18F-trifluoromethylation procedure. Issue 16 (9th April 2018) - King, Alice; Doepner, Andreas; Turton, David; Ciobota, Daniela M.; Da Pieve, Chiara; Wong Te Fong, Anne-Christine; Kramer-Marek, Gabriela; Chung, Yuen-Li; Smith, Graham
Abstract : Automated 18 F-trifluoromethylation provided the first radiosynthesis of [ 18 F]Trifluridine, which shows potential as a PET probe of drug mechanism of action. Abstract : Trifluoromethyl groups are widespread in medicinal chemistry, yet there are limited 18 F-radiochemistry techniques available for the production of the complementary PET agents. Herein, we report the first radiosynthesis of the anticancer nucleoside analogue trifluridine, using a fully automated, clinically-applicable 18 F-trifluoromethylation procedure. [ 18 F]Trifluridine was obtained after two synthetic steps in <2 hours. The isolated radiochemical yield was 3% ± 0.44 ( n = 5), with a radiochemical purity >99%, and a molar activity of 0.4 GBq μmol −1 ± 0.05. Biodistribution and PET-imaging data using HCT116 tumour-bearing mice showed a 2.5 %ID g −1 tumour uptake of [ 18 F]trifluridine at 60 minutes post-injection, with bone uptake becoming a prominent feature thereafter. In vivo metabolite analysis of selected tissues revealed the presence of the original radiolabelled nucleoside analogue, together with deglycosylated and phosphorylated [ 18 F]trifluridine as the main metabolites. Our findings suggest a potential role for [ 18 F]trifluridine as a PET radiotracer for elucidation of drug mechanism of action.